Determinación de la pertinencia del método de Harvard y la preparación de la negociación para la solución de conflictos funcionales. - Quezada Bijay, Franklin Fernando (My University, 2020)
The Harvard method represents one of the best tools for companies in conflict resolution, because it allows finding the best way to negotiate in a conflict. The main objective of this research is to determine the relevance of the negotiation preparation and Harvard's method in conflict resolution. In the work, the Harvard method templates were used to apply the elements in the given example of the New Esperanza banana marketing company. The type of investigation is qualitative, in which different investigations conducted for this case were analyzed. In preparation, the objectives, the place, with whom it is to be negotiated and the conditions that exist within it were analyzed. In addition, in the Harvard method the seven elements that are alternatives, interests, options, criteria, relationship, communication and commitment were used, with their respective templates to perform the example of functional conflict in the company. It was concluded that by making a good preparation and using the Harvard method as a tool for conflict resolution it is feasible, since it helps us find solutions where both parties are satisfied and everything is for the benefit of the organization.
El método de Harvard representa una de las mejores herramientas para las empresas en la solución de conflictos. El objetivo principal de esta investigación es determinar la pertinencia de la preparación de la negociación y el método de Harvard en la solución de conflictos. El tipo de investigación es cualitativa, en el que se analizó diferentes investigaciones realizadas con fines a este caso. En la preparación se analizaron los objetivos, el lugar y las condiciones que se dan dentro de la negociación. Además, en el método de Harvard se utilizó los siete elementos que son alternativas, intereses, opciones, criterios, relación, comunicación y compromiso, con sus respectivas plantillas para realizar el ejemplo de conflicto funcional en la empresa. Se determinó que realizar una buena preparación y utilizar el método de Harvard es factible como herramienta para la solución de conflictos, ya que nos ayuda a encontrar soluciones donde ambas partes involucradas queden satisfechas y sobre todo que la organización se vea beneficiada de estos acuerdos.
Keywords: NEGOCIACIÓN; MÉTODO DE HARVARD; PREPARACIÓN; CONFLICTO; ACUERDO